REDUPLIKASI BAHASA MADURA DI DESA SUNGAI ENAU SEBAGAI MODEL PEMBELAJARAN BERBASIS TEKS - Sumaiyah, Sumaiyah; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was focused on the reduplication of the Madurese language in the Sungai Enau village which was used by the Sungai Enau village community to communicate in everyday life. The purpose of this study was to describe the form of reduplication, describe the meaning of reduplication, and describe linguistic elements of reduplication in narrative text as a text-based learning model.  This study uses a descriptive method with a qualitative form. Sources of data in this study are speeches delivered by informants in Madura language in Sungai Enau Village. The techniques used are interview techniques, fishing techniques, and follow up techniques and techniques. Data collection tools in the form of interview instruments, image lists, and voice recording devices. Based on the results of data analysis on the word repeat of the Madurese language in Sungai Enau Village, this study collected three forms of repetitive words, namely repeated words, affixed repeated words, and the word repeat changed sound. The researcher produced narrative text as a supplement to the text of teaching materials. Keywords:       Madurese Language In The River Village Of Palm, Morphology, narrative text, Reduplication.